AN ANALYSIS OF VILLAGE FINANCIAL MANAGEMENT: THE IMPROTANCE OF REGULATIONS, VILLAGE FINANCIAL MANAGER COMPETENCIES AND COMMITMENT TO TASK IN KABUPATEN KONAWE SELATAN - Nita Hasnita; Mulyati Akib; Ernawati Ernawati; Rosnawintang Rosnawintang (Mega Aktiva, 2019)
This study aims to examine and analyze the variables that affect village financial management in Konawe Selatan village government especially in the aspects of village financial manager competence, commitment to tasks, and regulation. Data was collected by using questionnaires and documentation. The populations in this study were the Village Head, Village Secretary, Village Treasurer and Kasi/Kaur which numbered 1,344 people. The sampling technique by proportional stratified random sampling so that the overall number of respondents totaled 308 people. The analysis used multiple linear regression analysis with interaction test (Moderated Regression Analysis-MRA). The results showed that the competence of village financial managers had a positive and significant effect on village financial management while commitment to the task had a positive and not significant effect on village financial management. The MRA test results indicate that regulation cannot moderate the village financial manager competency variables and commitment to the task of village financial management. The adjusted R-Square value shows that the contribution of village financial manager competency variables, commitment to duties and regulations on village financial management variables is 47.5% and 52.5% of village financial management variables are influenced by other factors outside the model. Therefore, to improve village financial management in the Village Government in Kabupaten Konawe Selatan, it is necessary to consider village financial manager competencies in aspects of skills and experience, commitment to tasks on responsive aspects of change and sense of responsibility, and regulation on aspects of ease of implementation and understanding.